Fratria adotiva: percepções e vivências de irmãos mais velhos nas fratrias constituídas por adoção - Rocha, Berthane Gleide Feitosa Pinheiro (2009)
The entry of women into the market much more frequent; the development of new family configurations different from intact nuclear family; the strengthening of horizontal relationships are some of the contemporary social phenomena that focus on a lasting basis to relate to within of the family system, which is the fratrias. Furthermore, a very current issue, which attracts the attention of various social groups, is the adoption. The objective of this research was to investigate the relationship between the constituents in the fraternity, have they been established in biological or adoptive only by adoption. Sixteen people participated, divided between children, pre-adolescents and young adults of both sexes, aged from ten years, which responded to an interview focused on the arrival of the adoptive brother in the family. The interview was transcribed and their content was organized by themes. In the group of children and preadolescent we found that girls have most reception capacity and willingness to care. The fratrias consist solely of adoption had less conflicts then biological-adoptive. We also observed that in two ways to set up fratrias, the presence of feelings of mutual responsibility and care between brothers, in spite of references to moments of jealousy, conflict and competition. We hope that professionals and organizations which dealing with the issue of adoption could be benefited of this research data as well as professionals that work with children, adolescents and families. Also, we hope that it can contribute to the remission of some myths surrounding the adoption, pointing to a greater social awareness that it is a possibility of construction of family as healthy as the organic